Leadership in Action : Reader Forum - Leadership Training Comes Through in a Crisis - Bodie, Kevin (Center for Creative Leadership, 2001)
The Leadership Development program I participated in was about people-all people, and about how all people offer their own unique ways to help our causes, influence our behavior and decisions, and help make us all better people collectively.